Factor VIIa induces anti-inflammatory signaling via EPCR and PAR1 - Kondreddy, Vijay; Wang, Jue; Keshava, Shiva; Esmon, Charles T; Rao, L Vijaya Mohan; Pendurthi, Usha R (Blood, 2018)
Recent studies show that endothelial cell protein C receptor (EPCR) interacts with diverse ligands, in addition to its known ligands protein C and activated protein C (APC). We showed in earlier studies that procoagulant clotting factor VIIa (FVIIa) binds EPCR and downregulates EPCR-mediated anticoagulation and induces an endothelial barrier protective effect. Here, we investigated the effect of FVIIa's interaction with EPCR on endothelial cell inflammation and lipopolysaccharide (LPS)-induced inflammatory responses in vivo. Treatment of endothelial cells with FVIIa suppressed tumor necrosis factor α (TNF-α)- and LPS-induced expression of cellular adhesion molecules and adherence of monocytes to endothelial cells. Inhibition of EPCR or protease-activated receptor 1 (PAR1) by either specific antibodies or small interfering RNA abolished the FVIIa-induced suppression of TNF-α- and LPS-induced expression of cellular adhesion molecules and interleukin-6. β-Arrestin-1 silencing blocked the FVIIa-induced anti-inflammatory effect in endothelial cells. In vivo studies showed that FVIIa treatment markedly suppressed LPS-induced inflammatory cytokines and infiltration of innate immune cells into the lung in wild-type and EPCR-overexpressing mice, but not in EPCR-deficient mice. Mechanistic studies revealed that FVIIa treatment inhibited TNF-α-induced ERK1/2, p38 MAPK, JNK, NF-κB, and C-Jun activation indicating that FVIIa-mediated signaling blocks an upstream signaling event in TNFα-induced signaling cascade. FVIIa treatment impaired the recruitment of TNF-receptor-associated factor 2 into the TNF receptor 1 signaling complex. Overall, our present data provide convincing evidence that FVIIa binding to EPCR elicits anti-inflammatory signaling via a PAR1- and β-arrestin-1 dependent pathway. The present study suggests new therapeutic potentials for FVIIa, which is currently in clinical use for treating bleeding disorders.